Development of an expert advisor for Forex trading - Soh, Justin Ming Rui (Nanyang Technological University, 2020)
This report discusses the creation of a trading bot that trades using geometrical concepts. Citi Index Meta Trader 4 platform and Meta Editor, a programming editor, will be used for the creation of the bot. It will describe some of the current strategies used by Forex traders that are related to the topic of this report. A brief explanation of the Forex market will also provide some background to what a Forex market is. Following which, it will explore the use of geometrical concepts and how it can be applied for use by a trading bot. A vibrational concept and velocity concept were explored, and both were based on the graphs of the currency pair used. The report will include the prototyping process of the concept and problems faced. Subsequently, with a mid-project adjustment, the scope was widened to include other geometrical concepts for greater flexibility. The later concept uses velocity of the price change on the forex market. The trading bot was designed to use the change in price velocities to determine optimal trading positions.